2021
DOI: 10.1007/s00125-021-05608-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insufficient sleep on dysregulated blood glucose control under standardised meal conditions

Abstract: Aims/hypothesis Sleep, diet and exercise are fundamental to metabolic homeostasis. In this secondary analysis of a repeated measures, nutritional intervention study, we tested whether an individual’s sleep quality, duration and timing impact glycaemic response to a breakfast meal the following morning. Methods Healthy adults’ data (N = 953 [41% twins]) were analysed from the PREDICT dietary intervention trial. Participants consumed isoenergetic standardise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Further supporting the mechanism, recent evidence from 953 healthy adults showed that a person's deviation from their usual sleep pattern was associated with higher postprandial glucose level. 32 The present study was among the first to examine the relationships between objective sleep variables and continuous glucose outcomes among adults with T2D. Our data indicated that timing of nocturnal sleep was directly associated with glucose variability during the same night.…”
Section: Discussionmentioning
confidence: 55%
“…Further supporting the mechanism, recent evidence from 953 healthy adults showed that a person's deviation from their usual sleep pattern was associated with higher postprandial glucose level. 32 The present study was among the first to examine the relationships between objective sleep variables and continuous glucose outcomes among adults with T2D. Our data indicated that timing of nocturnal sleep was directly associated with glucose variability during the same night.…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, evidence has shown an association between sleep timing (i.e., bedtime and waketime) and dietary quality [ 64 , 65 ]. Although not yet fully understood, the causal pathway between dietary quality and sleep timing is mediated by biological mechanisms and hormonal responses, including postprandial glucose [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence has shown an association between sleep timing (i.e., bedtime and waketime) and dietary quality [ 64 , 65 ]. Although not yet fully understood, the causal pathway between dietary quality and sleep timing is mediated by biological mechanisms and hormonal responses, including postprandial glucose [ 64 , 65 ]. Results from the PREDICT dietary intervention trial, composed of participants from the United Kingdom and the United States of America, found an association between increased postprandial glucose levels, which are described as a spike in the amount of glucose found in one’s plasma shortly after a meal that can contribute to cardiovascular and diabetic complications potentially causing an offset of circadian rhythms, and later sleep midpoint [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in our cohort, post-menopausal females consumed higher intakes of dietary sugars and reported poorer sleep. These are both associated with more pronounced postprandial glycaemia 30 and increased risk of type-2 diabetes and cardiovascular disease. 31 Further, a decrease in physical activity energy expenditure and a shift to a more sedentary lifestyle associated with menopause 32 was recently demonstrated to be a direct effect of declining oestrogen 33 which may have been captured with more quantitative measures of physical activity in this study.…”
Section: Discussionmentioning
confidence: 99%